Digital platform regulation : global perspectives on internet governance - Terry Flew; Martin, Fiona R (Australia Palgrave Macmillan, 2022)
This is an Open Access book. Provides an in-depth exploration of global policy and governance issues related to digital platform regulation Connects research in platform studies to questions of public policy Explores a wide range of digital communication platforms such as social media, search engines and app stores.
Keywords: Social Sciences